Suportes organizacionais e aprendizagem de competências digitais de funcionários de um banco público brasileiro - Pinto, Francisco Maike Martins (2023)
This work aims to investigate the possible relations between organizational supports for learning and individual learning (acquisition) of digital skills in a financial institution. This is a quantitative, inferential, descriptive and explanatory research that addresses the digital skills highlighted in the bank's strategic planning. After collecting 201 questionnaires answered by bank employees, descriptive statistics, correlation and multiple regression analysis techniques were performed using SPSS 22.0 software. The results obtained indicated that, in the researched bank, there was a significant perception of offering material and psychosocial support for learning. It was also noticed that the acquired digital skills were applied in the day-to-day work at the institution. There was a significant relation between both supports and the acquisition of digital skills. Such findings reinforce the importance of providing a conducive work environment, with adequate material resources and a positive psychosocial environment, to facilitate learning and the development of digital skills among employees.